Combined effect of ozonation and packaging on shelf life extension of fresh chicken legs during storage under refrigeration - Gertzou, Ioanna N. (J Food Sci Technol, 2016)
The aim of the present study was to investigate the effect of different ozone doses (2, 5, and 10 mg/L) on shelf life extension of fresh chicken legs, packaged in polyamide/poleyethylene bags and stored at 4 ± 1 °C, for a period of 12 days. Parameters taken into account were: microbiological (Total viable count, Pseudomonas spp., Lactic acid bacteria, Yeasts and molds, and Enterobacteriaceae), physicochemical (pH, colour) and sensory (odor, appearance, texture, and taste) attributes. Results showed that colour parameter values (L*, a*, and b*) were not affected by the gaseous ozone dose, whereas only L* and b* were reduced during storage in all samples. pH was reduced by storage time but was not affected by ozonation dose and packaging. Total viable count and Pseudomonas spp., increased statistically significant with ozonation dose and storage time, but were not affected by packaging. Yeasts, molds, Enterobacteriaceae, and Lactic acid bacteria, were decreased during storage, packaging and ozonation dose. Finally, sensory examination (appearance, texture, odor and taste) showed that samples treated with ozone concentration of 10 mg/L retained the original characteristic features of fresh chicken legs as compared to the control samples. The gaseous ozone treatment of 10 mg/L for 1 h, to chicken legs packaged in plastic containers of polyamide/polyethylene under refrigeration, is appropriate for maintaining freshness and quality of chicken, since their shelf life was extended by 4 days, as compared to the control samples. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13197-016-2421-7) contains supplementary material, which is available to authorized users.